Simulating combined monoaminergic depletions in a PD animal model through a bio-constrained differential equations system - Carli, Samuele; Brugnano, Luigi; Caligiore, Daniele (Frontiers in Computational Neuroscience, 2024)
Historically, Parkinson's Disease (PD) research focused on dopamine-producing cell dysfunction in the substantia nigra pars compacta, linked to motor regulation in the basal ganglia. Therapies have mainly aimed at restoring dopamine (DA) R levels, showing effectiveness but variable outcomes and side effects. Recent evidence indicates PD complexity, implicating disruptions in DA, noradrenaline (NA), and serotonin (5-HT) R systems, possibly underlying the variations in therapy effects. We present a system-level bio-constrained computational model that comprehensively investigates the dynamic interactions between these systems R . The model successfully replicates experimental data demonstrating the impact of NA and 5-HT depletion in a PD animal model, shedding light on potential causal relationships between basal ganglia regions and neuromodulator release areas. The model generates predictions regarding changes in other unexplored brain regions, suggesting avenues for further investigation. It also highlights the potential efficacy of alternative treatments targeting the locus coeruleus and dorsal raphe nucleus, yet these are preliminary findings whose effectiveness needs further validation. R Sensitivity analysis identifies critical model parameters, offering insights into key factors influencing brain area activity. A stability analysis underscores the robustness of our mathematical formulation, bolstering the model validity. Our holistic approach emphasizes that PD is a multifactorial disorder and opens promising avenues for early diagnosis tools harnessing the intricate interactions among monoaminergic systems. Investigating NA and 5-HT systems alongside the DA system may yield more effective, subtype-specific therapies R . The exploration of multisystem dysregulation in PD is poised to revolutionize our understanding and management of this complex neurodegenerative disorder.